Electronic textbook use in the information–educational environment - Богославець, Л. П. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2014)
The article is devoted to the urgent problem of the electronic textbook using as an effective apparatus in the information–educational environment. The experience of electronic textbook applying has been analysed in the article, the definition of the electronic textbook has been given and its structure and role in the educational process have also been described in the article. The stages of developing an electronic textbook have been considered in details. The reasons for introducing an electronic textbook for students of different forms of education to the modern educational system have been disclosed